The sound of power: conveying and detecting hierarchical rank through voice. - Ko, Sei Jin; Sadler, Melody S; Galinsky, Adam D (Psychol Sci, 2015)
The current research examined the relationship between hierarchy and vocal acoustic cues. Using Brunswik's lens model as a framework, we explored how hierarchical rank influences the acoustic properties of a speaker's voice and how these hierarchy-based acoustic cues affect perceivers' inferences of a speaker's rank. By using objective measurements of speakers' acoustic cues and controlling for baseline cue levels, we were able to precisely capture the relationship between acoustic cues and hierarchical rank, as well as the covariation among the cues. In Experiment 1, analyses controlling for speakers' baseline cue levels found that the voices of individuals in the high-rank condition were higher in pitch and loudness variability but lower in pitch variability, compared with the voices of individuals in the low-rank condition. In Experiment 2, perceivers used higher pitch, greater loudness, and greater loudness variability to make accurate inferences of speakers' hierarchical rank. These experiments demonstrate that acoustic cues are systematically used to reflect and detect hierarchy.